2020
DOI: 10.1080/15622975.2020.1747114
|View full text |Cite
|
Sign up to set email alerts
|

Executive functioning and emotion recognition in youth with oppositional defiant disorder and/or conduct disorder

Abstract: Objectives: Executive functioning and emotion recognition may be impaired in disruptive youth, yet findings in oppositional defiant disorder (ODD) and conduct disorder (CD) are inconsistent. We examined these functions related to ODD and CD, accounting for comorbid attention-deficit/hyperactivity disorder (ADHD) and internalising symptoms. Methods: We compared executive functioning (visual working memory, visual attention, inhibitory control) and emotion recognition between youth (8-18 years old, 123 boys, 55 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…Regarding ODD, while executive function difficulties focus mainly on "hot" executive functions, which are the functions related to emotional involvement (Rubia, 2011), they also include "cool" executive functions, which are those related to tasks requiring cognitive, critical, or logic analysis without the intervention of emotions. Accordingly, difficulties in cognitive reappraisal, rumination, expressive suppression, emotion dysregulation, planning (Jiang et al, 2016), inhibitory control (Deters et al, 2020), working memory and sustained attention (Schoorl et al, 2018), emotion processing, error monitoring, problem solving, and self-control (Noordermeer et al, 2016) have been reported in children with ODD. The results of this study indicate that executive functions difficulties are not characteristic of OCP, since executive functioning is similar in OCP and in the all-low classes (classes 2 and 1), while the four global indexes of executive functioning are significantly higher when there is a confluence of oppositional dimensions at a high level and OCP (class 4).…”
Section: Sdq-teachers -M (Sd)mentioning
confidence: 99%
“…Regarding ODD, while executive function difficulties focus mainly on "hot" executive functions, which are the functions related to emotional involvement (Rubia, 2011), they also include "cool" executive functions, which are those related to tasks requiring cognitive, critical, or logic analysis without the intervention of emotions. Accordingly, difficulties in cognitive reappraisal, rumination, expressive suppression, emotion dysregulation, planning (Jiang et al, 2016), inhibitory control (Deters et al, 2020), working memory and sustained attention (Schoorl et al, 2018), emotion processing, error monitoring, problem solving, and self-control (Noordermeer et al, 2016) have been reported in children with ODD. The results of this study indicate that executive functions difficulties are not characteristic of OCP, since executive functioning is similar in OCP and in the all-low classes (classes 2 and 1), while the four global indexes of executive functioning are significantly higher when there is a confluence of oppositional dimensions at a high level and OCP (class 4).…”
Section: Sdq-teachers -M (Sd)mentioning
confidence: 99%
“…For example, a previous study adopting the dot-probe paradigm found that adolescents with CD showed attentional avoidance of angry, fearful and happy faces compared to typically developing adolescents recruited from schools and colleges ( 47 ). Another study revealed that youths with CD showed impairments in recognition of anger, disgust, fear, happiness, sadness and surprise, compared with typically developing controls ( 109 , 110 ). One possible reason for the difference between these results and ours might be the influence of peers and the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Based on both the RNR model [15] and the socio-ecological model [14], FAST subgoals have been formulated based on the dynamic risk and protective factors at the level of the individual, family, and the broader system of the juvenile to reach intervention goals. At the individual level, FAST aims to target juvenile criminogenic risk factors related to psychological functioning such as cognitive distortions [17][18][19] and low executive functions such as cognitive exibility, inhibition [20,21] and coping skills [22,23]. In addition, FAST aims to effectuate adequate daytime activities [18,24].…”
Section: Intervention Subgoalsmentioning
confidence: 99%